Pengelolaan Sistem Rekrutmen dan Penempatan Guru di MI Al-Mukhlisin Kota Jambi - Najmul Hayat; Riftiyanti Savitri; Nuraini (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to find out and discuss the management in the recruitment and placement of teachers in Madrasah Ibtidaiyah Al-Mukhlisin Jambi City. This research uses a descriptive qualitative approach, with observational research methods, interviews, and documentation. The source of the data was obtained from the Head of the Madrasah, a Teacher who has taught in a Madrasah, and a new Teacher in a Madrasah. The results showed that: 1) The process of implementing teacher recruitment and placement was carried out by the Head of Madrasah and Foundation; 2) Recruitment is carried out when the Madrasa needs a vacant position, and the dissemination of recruitment information in the can be orally; 3) The placement of teachers is carried out by the Head of the Madrasah taking into account the place of residence of the applicant; 4) The obstacle encountered in the recruitment and placement of teachers is that information is not widely spread.